European Integration: from Christian Values to the Secular State - V. P. Kirilenko; G. V. Alekseev (Евразийская интеграция: экономика, право, политика, 2019)
Prime value for the European integration has a ratio of Christian values and the moral of the secular state. By means of diplomatic tools, the Moscow principality finds the imperial architecture necessary for completion of integration process of collecting of Russian lands to the uniform state.